1972
DOI: 10.1007/bf01645526
|View full text |Cite
|
Sign up to set email alerts
|

Exact gravitational field of the infinitely long rotating hollow cylinder

Abstract: The vacuum line element inside an infinitely long rotating hollow cylinder is the usual flat space line element. It is fitted in a most general way to the general cylindrical vacuum field outside at the singular hypersurface R o = const, representing the infinitely thin hollow cylinder. With the use of the jump conditions at R o = const the surface densities τ x μ , of which the energy-momentum-stress tensor τ^ of the shell consists, are calculated. The physical properties of the cylinder, as derived from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 14 publications
1
19
0
Order By: Relevance
“…Hence the spacetime is flat inside the shell (R = 0) and the exterior field is static ( B = 0). These conclusions agree with the results of the exact theory [6][7][8], though the general situation is more complicated [6].…”
Section: Introductionsupporting
confidence: 89%
“…Hence the spacetime is flat inside the shell (R = 0) and the exterior field is static ( B = 0). These conclusions agree with the results of the exact theory [6][7][8], though the general situation is more complicated [6].…”
Section: Introductionsupporting
confidence: 89%
“…Let us for convenience translate the radial coordinate r (which is defined by the parametrization (2.1) only up to an additive constant) so that the surface r = 0 corresponds to the cylinder surface. As in Frehland's analysis of the hollow cylinder problem [3], we use the junction method [5] to determine the space-time metric, i. e. the 3 × 3 matrix λ(r), from the knowledge of the energy-momentum tensor T µ ν = κ −1 T µ ν δ(r) concentrated on the surface of the matter cylinder. The metric field λ(r) may be written…”
Section: )mentioning
confidence: 99%
“…A limiting case which may be of some interest is that of a hollow cosmic string, the energy-momentum tensor being concentrated not on a line but on the surface of an infinitely long cylinder. The gravitational field generated by such a cylinder with given energy density and longitudinal and azimuthal stresses, and rotating about its axis, was in principle determined some time ago by Frehland [3]. One of the results of Frehland's analysis is that, unexpectedly, a rotating hollow cylinder can exist in general relativity only if its energy-momentum is traceless.…”
Section: Introductionmentioning
confidence: 99%
“…It can be shown that the eigenvalue λ = 0 corresponds to the eigenvector ξ µ 1 = η µ , where η µ is the normal vector to the hypersurface r = R(t), and given by Eq. (29). The eigenvalue λ = p z corresponds to the eigenvector ξ µ 2 = z µ , which represents the pressure of the shell in the z-direction.…”
Section: Rotating Cylindrical Shellsmentioning
confidence: 99%